A simple marking system for accurate intraoperative monitoring and adjustment of cyclotorsion strabismus surgery - Lung-Chi Lee; Hsu-Chieh Chang; Hsu-Chieh Chang; Yi-Hao Chen; Ke-Hung Chien (Frontiers in Medicine, 2023)
Ocular cyclotorsion is treatable only with surgery. The surgical procedure must be tailored individually to the specific etiologies causing the horizontal and vertical strabismus and its torsional components. An adjustable surgical approach is often used for postoperative or intraoperative adjustments. However, the methods currently used have some limitations. In this study, we propose a simple intraoperative marking system for all cyclotorsion correction surgery. The proposed marking system used three sets of surface markers: external horizontal markings, ocular horizontal markings, and surgical torsion markings, drawn in sequence. We retrospectively analyzed the surgical results using this novel marking system in this single-center, single-surgeon study. Fifteen patients with cyclotorsion who underwent treatment using the proposed marking system as an intraoperative aid between August 2019 and August 2021 were included. The medical charts were thoroughly reviewed, and the pre-and postoperative subjective and objective cyclotorsion were analyzed. Among the study subjects (10 males, 5 females; age range: 6–89 years), 13 had excyclotorsion and 2 incyclotorsion. Preoperative mean net subjective cyclotorsion measured by the double Maddox rod (DMR) test was 6.0° (standard deviation: 10.8°) and mean net disc-to-fovea angle (DFA) was 20.23° (13.21°). The postoperative net DMR and DFA were 0.2° (2.1°) and 14.09° (5.97°), respectively. The mean absolute net DMR and DFA being treated were 9.8° (4.8°) and 9.76° (4.61°). Overall, the proposed intraoperative marking system is a simple and quantitative method to assess, monitor, and adjust the torsional aspect for all strabismus surgeries.